Developing a Proficient and Motivated Teacher Workforce in the Philippines - World Bank Group (World Bank, Washington, DC, 2016)
Over the last decade, research from many different countries has demonstrated the important role played by teachers in increasing students’ learning and improving their academic performance. Studies from countries as different as the US and Indonesia have shown the enormous benefits that follow from having adequate and effective teachers working in a country’s schools. In Indonesia, a value-added analysis of student learning outcomes found that the more teachers know, the greater the improvements in the learning competencies of primary and junior secondary students. In the US, better teaching in elementary and secondary schools has been shown to increase students’ college participation rates, raise their subsequent earnings, and improve other long-term outcomes. Providing teachers with good quality professional development opportunities has been shown to be an effective way of increasing their competencies and improving student learning outcomes in many different settings. A series of systematic reviews have been undertaken recently to assess the impact of different interventions on student learning outcomes in developing countries. One of the most consistent findings from these reviews has been the positive and significant impact that interventions to strengthen teaching practice, introduce innovative instructional methods, and strengthen teachers’ subject knowledge can have on student learning. However, in many countries, such professional development opportunities frequently fail to meet even minimum levels of quality and fall short of what teachers want and need.